2016
DOI: 10.1016/j.antiviral.2016.07.008
|View full text |Cite
|
Sign up to set email alerts
|

JNJ872 inhibits influenza A virus replication without altering cellular antiviral responses

Abstract: JNJ-63623872 (formally known as VX-787; referred to here as JNJ872) is an orally bioavailable compound, which is in phase II clinical trials for the treatment of influenza A virus (IAV) infections. Here we show that JNJ872 inhibits at nanomolar concentrations the transcription of viral RNA in IAV-infected human macrophages by targeting a highly conserved site on the cap-snatching domain of influenza polymerase basic 2 protein (PB2). Furthermore, even lower concentrations of JNJ872 protected macrophages from IA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
57
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 43 publications
4
57
0
Order By: Relevance
“…[10][11][12][13]. These molecules should be first evaluated in vitro using antiviral efficacy assays, and then in animal models as described in our previous studies [14].…”
Section: Combination Of Various Omics Techniques Identifies Potentialmentioning
confidence: 99%
See 3 more Smart Citations
“…[10][11][12][13]. These molecules should be first evaluated in vitro using antiviral efficacy assays, and then in animal models as described in our previous studies [14].…”
Section: Combination Of Various Omics Techniques Identifies Potentialmentioning
confidence: 99%
“…In particular, our recent transcriptomics study identified a total of 126 genes which were up-or down-regulated greater than four-fold in A/Udorn/1972(H3N2) or A/WSN/1933(H1N1) virus infected human peripheral blood mononuclear cells (PBMC)-derived macrophages compared to mock-infected cells at 8 h post infection (p < 0.05) [10]. The most significant canonical pathways specifically associated with virus infections, according to gene set enrichment analysis (GSEA; www.broadinstitute.org/gsea, [16]), were interferon-α, -β, and -γ signaling, cytokine signaling, [10][11][12][13].…”
Section: Combination Of Various Omics Techniques Identifies Potentialmentioning
confidence: 99%
See 2 more Smart Citations
“…IAV also actively exploits cell metabolism for the production of viral RNA, proteins, and lipids [24,26,[31][32][33][34][35][36]. Free NTPs are used by viral polymerase which produces vRNA and its replication intermediates.…”
mentioning
confidence: 99%